Econometrics Analysis of Financial Development and Economic Growth: Evidence from Nigeria (Global Journal of Management and Business Research, 2018)
This work explored the relationship between financial development and economic growth in Nigeria. Specifically it investigated the extent to which financial development engenders economic growth. It also verified the existence of supply leading and/or demand following hypothe
Keywords: financial development; economic growth; supply leading; demand following hypotheses; cointegration